2022
DOI: 10.3390/foods11152319
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Antifungal Activity of Pullulan Edible Films Enriched with Propolis Extract for Active Packaging

Abstract: Active pullulan films with the addition of 3, 5 or 10% propolis extract produced by the casting method were tested in the study. Propolis extracts from Bochnia County, Siedlce County and Ełk County (Poland) were used. The appearance of the films was characterized, as well as physical parameters (thickness, moisture content, water solubility), tensile strength (TS), elongation at break (EB), optical characteristics (light transparency, UV barrier, color) and antifungal properties. The antifungal activity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 70 publications
1
7
0
2
Order By: Relevance
“…The strongest antifungal effect was observed in samples S1, S4 and S5, with the last two being obtained from the same locations as honey samples S4 and S5, which also presented the strongest antifungal effect, confirming the fact that the geographical area and botanical origin can influence the antimicrobial properties of honey and propolis. Moreover, in the case of propolis, our study confirms previous studies on the effect of some propolis samples on fungal strains [ 28 , 52 ].…”
Section: Discussionsupporting
confidence: 90%
“…The strongest antifungal effect was observed in samples S1, S4 and S5, with the last two being obtained from the same locations as honey samples S4 and S5, which also presented the strongest antifungal effect, confirming the fact that the geographical area and botanical origin can influence the antimicrobial properties of honey and propolis. Moreover, in the case of propolis, our study confirms previous studies on the effect of some propolis samples on fungal strains [ 28 , 52 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the dominant content of caffeic acid and its derivatives was found. Moreover, cichoric acid was identified in all the tested urban propolis extracts, which was first identified in propolis from agricultural areas in Poland [ 21 , 22 , 23 , 24 ]. Research by Wozniak et al [ 25 ] showed a high content of epicatechin, catechin, pinobanksin, myricetin and vanilla and syringic acids in propolis from agricultural areas in Poland, these chemical components were also identified in propolis from urban apiaries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study confirms our previous results on the effect of some propolis samples on fungal strains [ 25 ], as well as other studies on Alternaria spp., Fusarium spp., Mucor spp., and Aspergillus spp. [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%